1997
DOI: 10.2169/internalmedicine.36.865
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bronchofiberscopy for Diagnosis of Allergic Bronchopulmonary Aspergillosis.

Abstract: To assess the use of bronchofiberscopy for the diagnosis of allergic bronchopulmonary aspergillosis (ABPA), we retrospectively analyzed bronchofiberscopic and pathologic findings of specimens obtained by bronchofiberscopy in 8 patients who met the British criteria for ABPA.Two of the 8 patients completely met Rosenberg's primary criteria for ABPA,while the remaining 6 lacked only 1 or 2 immunologic and radiographic conditions of the criteria. Bronchofiberscopic inspection revealed the presence of mucus plugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Therefore, the importance of mucous plugs for diagnosing ABPM should be reconsidered. Our study indicates that, with an aggressive investigation of mucous plugs, some patients can be diagnosed as having ABPM before serum immunological tests turn positive (33). However, typical pathological findings were detected in 17 of the 41 patients in the present study, which indicates that the use of other investigational methods is required.…”
Section: Discussioncontrasting
confidence: 52%
“…Therefore, the importance of mucous plugs for diagnosing ABPM should be reconsidered. Our study indicates that, with an aggressive investigation of mucous plugs, some patients can be diagnosed as having ABPM before serum immunological tests turn positive (33). However, typical pathological findings were detected in 17 of the 41 patients in the present study, which indicates that the use of other investigational methods is required.…”
Section: Discussioncontrasting
confidence: 52%
“…Bronchoscopy has been shown to have a role in the diagnosis of ABPA (72,73), especially in patients with atypical manifestations and those who do not meet the standard diagnostic criteria (see below). Bronchoscopic examination in these two studies (72,73) revealed evidence of mucous plugging.…”
mentioning
confidence: 99%
“…Bronchoscopy and BALF are helpful for the diagnosis and evaluation of patients with eosinophilic lung diseases, especially those with atypical manifestations[ 9 , 10 ]. In healthy individuals, the eosinophil percentage in BALF is < 1%.…”
Section: Discussionmentioning
confidence: 99%